Gordura protegida de óleo de palma na alimentação de ovelhas Lacaune em lactação - Bianchi, Anderson Elias (2014)
The dairy sheep business, common activity in European and Asian countries, has been growing in recent years in Brazil. In addition to producing milk with high solids contents, its derivatives are considered functional foods because of the health benefits. Thus, the objective of this study was to evaluate the levels of palm oil in protected form in the feeding of lactating ewes of the Lacaune breed on body dynamics, production and milk composition. Four treatments were used with nine replications, with treatments consisting of 0.0%, 2.0%, 4.0% and 6.0% fat protected palm oil in concentrated animal. The diet was formulated and adjusted per animal after weighing the milk, isoproteic, isoenergetic with the same forage / concentrate ratio, using corn silage as roughage in all treatments. The weight of milk and collection for analysis of chemical composition seven weeks of lactation and every fortnight in subsequent weeks were performed weekly during the first, and the experimental period comprised the whole lactation period of 182 days. The increased levels of protected fat in the diet resulted in less weight gain and lower body condition of the animals (P<0.05). Treatment with 6% protected fat showed the highest milk yield (P<0.05). The fat content in milk had a positive linear effect (P<0.05), whereas the content of protein, lactose and solids nonfat showed negative linear effect (P< 0.05). The content of total solids in milk, had no effect (P>0.05). In relation to the total production of milk solids (fat, protein, lactose, total solids and solids non fat) had no effect (P>0.05) in any variable. The use of protected fat from palm oil is efficient to increase the production of milk fat and sheep Lacaune.